Analysis of Reading Interest in Grade 3 Students of Rade Elementary School - Yunita Yunita; Azra Fauzi; Yuyun Yuningsih (Jurnal Ilmiah Mandala Education (JIME), 2025)
This study aims to describe the reading interest of students in grade III of elementary school. This type of research uses a descriptive method with a qualitative approach. The subjects of this study were grade III students and their homeroom teachers. Data collection techniques in this study used interviews, documentation, and questionnaires. The results of the study indicate that the reading interest of students in grade III is good. This is evidenced by the results of the questionnaire for grade III with a total of 15 students. Only 9 students received the highest score, meaning they have a good reading interest. 4 students received a moderate score, meaning they have a fairly good reading interest. 2 students received the lowest score, meaning they have a low reading interest. This can be seen from the results of the questionnaire obtained from students. From the results of the interview, it was found that teachers always get students used to reading before studying for 15 minutes and that there are supporting factors in increasing students' reading interest, namely: reading 15 minutes before learning and intensive teacher guidance.